Analisis Persepsi Penggunaan Aplikasi Mobile JKN di Puskesmas Jatiwarna Dengan Pendekatan Teori Technology Acceptance Model (TAM) - Ilma Aulia Rahma; Daniel Happy Putra; Bangga Agung Satrya; Laela Indawati (Jurnal Manajemen Informasi dan Administrasi Kesehatan (JMIAK), 2026)
The Mobile JKN application is an innovation by BPJS Kesehatan to facilitate access to health services. This study aims to analyze perceptions of the use of the Mobile JKN application at the Jatiwarna Community Health Center using the Technology Acceptance Model (TAM) approach, which includes Perceived Usefulness (PU), Perceived Ease of Use (PEOU), and Behavioral Intention to Use (BIU). The research method used was quantitative descriptive with a survey technique, involving 96 respondents. The data collection instrument was a questionnaire with a Likert scale. The results showed that most respondents had good perceptions of the usefulness and ease of use of the Mobile JKN app. Spearman's correlation test indicated a significant positive relationship between PU and BIU, as well as between PEOU and BIU. In conclusion, the higher the perception of the app's usefulness and ease of use, the higher the behavioral intention to use it. These findings are important in supporting the digitalization of healthcare services and improving the effectiveness of the Mobile JKN implementation.